Peran Mahasiswa KKN guna Meningkatkan Kesadaran Kesehatan Mental dan Pencegahan Perundungan untuk warga IOM SURABAYA di Desa Sawotratap Kecamatan Gedangan Kabupaten Sidoarjo - Aristawidyana Salsabila; Putri, Seftia Aulia; Petrasia Yao; Ricky Alejandro Martin (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) conducted by students of Universitas 17 Agustus 1945 Surabaya at IOM SURABAYA aimed to increase public awareness of the importance of mental health and bullying prevention. The program was designed using an educational and participatory approach, targeting children, adolescents, and parents living in the refugee area of IOM in Sawotratap Village, Gedangan District, Sidoarjo Regency. The activities included bullying awareness sessions, stress management education, individual counseling, relaxation training, group coloring, and bead bracelet-making as therapeutic tools. The findings showed that participants experienced an increase in their understanding of bullying behavior, early symptoms of stress, and practical strategies for emotional regulation. Children demonstrated a growing confidence in expressing their experiences with bullying, while parents gained new knowledge on how to manage stress within the household. Creative activities such as coloring and beading were effective in providing a safe space for self-expression, enhancing social interaction, and promoting psychological well-being. Overall, this program illustrates that simple, context-sensitive interventions can produce meaningful psychosocial impacts and serve as an entry point for sustainable community empowerment. It is recommended that similar approaches be adopted in other vulnerable communities to foster inclusive, mentally resilient environments.